Heart rate as an indicator for exercise prescription for normal, overweight, and obese adolescents - Kamilla Bolonha Gomes; Anselmo José Perez; Luciana Carletti; Adilson Marques (Universidade Estadual Paulista (UNESP), 2016)
Abstract This study aimed to investigate the relationship between heart rate (HR) predicted and VO2max using a CPET (cardiopulmonary exercise testing) among normal weight, overweight, and obese adolescents. The sample comprised 299 adolescents (142 boys), from Vitória (ES, Brazil), aged 10-14 years (12.6±1.4). Adolescents were classified into normal weight (n=236), overweight (n=34), and obese (n=29). Adolescents were subjected to a CPET ramp protocol on a treadmill. It was observed that the reserve heart rate (HRres) was similar to the maximum recommended oxygen uptake (VO2) for the maintenance and improvement of cardiorespiratory fitness. It was also observed that HRres can be used to control the intensity of exercise sessions in physical education classes independent of weight status. In conclusion, the relationship between the HR and VO2 for adolescents is linear, allowing the level of intensity to be determined by the HRres proportion related with the correspondent %VO2max levels of intensity, according to BMI-for-age categories.